Assessment of landmark detection in cephalometric radiographs with different conditions of brightness and contrast using the an artificial intelligence software - Santos Menezes, Liciane dos; Silva, Thaísa Pinheiro; Lima dos Santos, Marcos Antônio; Hughes, Mariana Mendonça; Reis Mariano Souza, Saulo dos; Leite Ribeiro, Patrícia Miranda; Luiz de Freitas, Paulo Henrique; Takeshita, Wilton Mitsunari [UNESP] (Oxford University Press (OUP), 2023)
Objectives To evaluate the reliability and reproducibility of an artificial intelligence (AI) software in identifying cephalometric points on lateral cephalometric radiographs considering four settings of brightness and contrast. Methods and materials Brightness and contrast of 30 lateral cephalometric radiographs were adjusted into four different settings. Then, the control examiner (ECont), the calibrated examiner (ECal), and the CEFBOT AI software (AIs) each marked 19 cephalometric points on all radiographs. Reliability was assessed with a second analysis of the radiographs 15 days after the first one. Statistical significance was set at p < 0.05. Results: Reliability of landmark identification was excellent for the human examiners and the AIs regardless of the type of brightness and contrast setting (mean intraclass correlation coefficient >0.89). When ECont and ECal were compared for reproducibility, there were more cephalometric points with significant differences on the x-axis of the image with the highest contrast and the lowest brightness, namely N(p = 0.033), S(p = 0.030), Po(p < 0.001), and Pog’(p = 0.012). Between ECont and AIs, there were more cephalometric points with significant differences on the image with the highest contrast and the lowest brightness, namely N(p = 0.034), Or(p = 0.048), Po(p < 0.001), A(p = 0.042), Pog’(p = 0.004), Ll(p = 0.005), Ul(p < 0.001), and Sn(p = 0.001). Conclusions While the reliability of the AIs for cephalometric landmark identification was rated as excellent, low brightness and high contrast seemed to affect its reproducibility. The experienced human examiner, on the other hand, did not show such faulty reproducibility; therefore, the AIs used in this study is an excellent auxiliary tool for cephalometric analysis, but still depends on human supervision to be clinically reliable. Dentomaxillofacial Radiology (2023) 52, 20230065. doi: 10.1259/dmfr.20230065 Cite this article as: Menezes LS, Silva TP, Lima dos Santos MA, Hughes MM, Mariano Souza SR, Leite Ribeiro PM, et al. Assessment of landmark detection in cephalometric radiographs with different conditions of brightness and contrast using the an artificial intelligence software.
Keywords: Artificial intelligence; Cephalometry; Dental radiography; Machine learning; Radiology; Reproducibility of results